2019
DOI: 10.1016/j.midw.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Can common characteristics be identified as predictors for seasonal influenza vaccine uptake in pregnancy? A retrospective cohort study from a South London Hospital

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Since the information often given to patients on maternal vaccination is often affected by personal perceptions, it is essential to educate all healthcare professionals on current guidelines, especially midwives, who have reported little undergraduate training on maternal vaccination [40] . Maternal age, parity, ethnicity and deprivation level have also been associated with vaccine coverage in other studies [41] , [42] , [43] , but were not identified in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Since the information often given to patients on maternal vaccination is often affected by personal perceptions, it is essential to educate all healthcare professionals on current guidelines, especially midwives, who have reported little undergraduate training on maternal vaccination [40] . Maternal age, parity, ethnicity and deprivation level have also been associated with vaccine coverage in other studies [41] , [42] , [43] , but were not identified in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…Outside of the US, several studies identified race as factor impacting vaccine uptake. In the UK, white British women are more likely to be vaccinated or to intend to receive a vaccine during pregnancy than other races (Byrne et al, 2018 ; Campbell et al, 2015 ; Carlisle et al, 2019 ; McAuslane et al, 2018 ; McQuaid et al, 2018 ) In Malaysia willingness to be vaccinated against a hypothetical ZIKA vaccine differed by ethnic group (Wong et al, 2017 ) In France, North African or Asian origin was associated with lack of vaccination against pandemic H1N1 (Freund et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain. 36 The main characteristics of the included studies are summarized in Tables 1 and S2.…”
Section: Re Sultsmentioning
confidence: 99%